Near‐Infrared Electroluminescence beyond 800 nm with High Efficiency and Radiance from Anthracene Cored Emitters. Issue 48 (16th November 2020) - Yu, You‐Jun; Hu, Yun; Yang, Sheng‐Yi; Luo, Wei; Yuan, Yi; Peng, Chen‐Chen; Liu, Jin‐Feng; Khan, Aziz; Jiang, Zuo‐Quan; Liao, Liang‐Sheng
Abstract: Derivatives based on anthryleno[1, 2‐b]pyrazine‐2, 3‐dicarbonitrile (DCPA) are used as luminescent materials, to realize near‐infrared (NIR) electroluminescence. By functionalizing DCPA with aromatic amine donors, two emitters named DCPA‐TPA and DCPA‐BBPA are designed and synthesized. Both molecules have large dipole moments owing to the strong intramolecular charge transfer interactions between the amine donors and the DCPA acceptor. Thus, compared with doped films, the emission of neat films of DCPA‐TPA and DCPA‐BBPA can fully fall into the NIR region (>700 nm) with increasing surrounding polarity by increasing doping ratio. Moreover, the non‐doped devices based on DCPA‐TPA and DCPA‐BBPA provide NIR emission with peaks at 838 and 916 nm, respectively. A maximum radiance of 20707 mW Sr −1  m −2 was realized for the further optimized device based on DCPA‐TPA. This work provides a simple and efficient strategy of molecular design for developing NIR emitting materials. Abstract : Highly luminescent anthracene is incorporated in designing near‐infrared (NIR) molecules. Flanked with donor and acceptor units, the emitters, named DCPA‐TPA and DCPA‐BBPA with strong dipole moment, were constructed to realize NIR electroluminescence. Their non‐doped devices can achieve high radiance and efficiency with nearly all the emission in the NIR region (>700 nm).